Estudo da permeabilidade e estrutura de solo-cal - Silveira, Juçara da (1979)
A study of changes in perrneability and structure of a soil when stabilized with lime is the objective of this thesis. First, a bibliographic review is made on permeability of clay soils, and the modifications of physical soil properties due to lime treatment. A special permeameter was built which uses compressed air and permits saturation by back pressure. This apparatus is described and its use in routine work is explained. The permeability study was divided into three steps: first, the testing of pure soil samples; second, testing os soil-lime with no curing; and third, soil-lime after curing. All samples were compacted by kneading. Permeability and compaction curves are presented. Results show an increase in soil permeability when the soil is treated with lime. Such an increase is greater for high moisture contents, and curing has little effect on it. Finally, a study of soil structure was made by using the scanning eletronic microscope. Structures of pure soil and soil-lime were compared.